Enhancing Local Tourism Through AI-Powered Mobile Application (International Journal of Environmental Sciences, 2025)
Backgrounds: With increasing digitalization, tourism has become more globalized, but the potential of local tourist spots remains untapped because of visibility deficit and lack of personal guidance. In this paper, a mobile app based on AI is suggested to enable local tourism through crowd engagement and artificial intelligence. The app features geolocation-based suggestions, landmark detection using image recognition, and personalized suggestions based on user activity and preference. The app also allows users to share pictures, reviews, and insider tips, making the tourism experience dynamic and continually evolving. Utilizing machine learning techniques and crowd-sourced data, the app seeks to provide residents and travellers alike with value- added, personalized experiences. The solution proposed places emphasis on accessibility, cultural preservation, and local economic growth. In this paper, the theoretical framework, system design, and AI-based methods utilized in the app are described. The app seeks to illustrate how technology can close the loop between visitors and unknown yet culturally significant places, enabling sustainable tourism development.